Sex Ratio and Global Sodomy Law Reform in the Post-WWII Era - Simon Chang (Global Labor Organization (GLO), 2020)
This paper studies the role of population sex ratio, i.e. ratio of men to women, in the global wave of sodomy law reform in the post-WWII era. Using a global survey, this paper first finds that men are more homophobic than women and such pattern has persisted across countries and time. With a newly constructed panel data of 183 countries, this paper then finds that high sex ratio causally makes sodomy law less likely to be repealed. The result is robust to numerous checks, including using temperature as an instrumental variable for sex ratio.
Keywords: J16; J18; K14; 330; Sex Ratio; Sodomy Law; Gay Rights; Homophobia